Efektivitas Penyelesaian Layanan Aspirasi dan Pengaduan Online Rakyat di Kota Tanjungpinang Tahun 2023 - Stevy Indah Pratama; Nazaki Nazaki; Khairi Rahmi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
SP4N-LAPOR is a platform developed by the Ministry of Administrative and Bureaucratic Reform to facilitate the public in submitting complaints, aspirations, and suggestions related to public services. The number of SP4N-LAPOR! reports in Tanjungpinang City was 252 reports from 2019 to 2023. In 2023, the number of reports increased by 73. Based on data and information gathered during the preliminary research, out of the 73 reports, 54 were completed, 12 were processed, and 7 were archived. The increase in the number of reports prompted the researcher to examine the effectiveness of the resolution process. The research question in this study is: How effective is the resolution of public grievances and complaints through online services in the city of Tanjungpinang in 2023? This study aims to analyze the effectiveness of the resolution of public aspirations and complaints online at several agencies in Tanjungpinang City in 2023. The theory used in this study is Campbell J.P.'s theory, which consists of four aspects: program success, target success, input and output levels, and overall goal achievement. The method used is a qualitative approach. The research results from the program success indicators show that the steps taken in verifying and resolving reports are in accordance with the SP4N-LAPOR! SOP. In the target success indicators, the researcher found that all complaint reports for 2023 have been completed. Although there are still some unfinished reports on the SP4N-LAPOR! website, they are still being followed up by the relevant agencies.